Strengthening Indonesia's Defense Industry through Strategic Insights from Japan’s Defense Systems - Djansena, Alradix; Erika, Katherine; Adhilni, Robbi; Ronaldi, Tomy; Kartiningsih, Yuli; Ghazalie, Ghazalie (LPPM Institut Pendidikan Nusantara Global, 2025)
Indonesia's defense industry faces significant challenges in achieving self-reliance, including a heavy dependence on imported military technology, which limits its strategic autonomy and industrial competitiveness. This research analyzes how Indonesia can strengthen its defense industry by leveraging strategic insights from Japan’s defense systems. This country has successfully built an advanced defense industry despite constitutional constraints. The study employs a qualitative method, focusing on literature review and secondary data from various sources. The findings suggest that Japan’s collaboration model, which involves the government, private sector, and academia, can be adopted in Indonesia. Technology transfer strategies and dual-use technologies can foster innovation and reduce import reliance. The implications of this research highlight the importance of increasing investment in research and development (R&D) and expanding international cooperation to enhance Indonesia’s defense industry self-reliance.